1974
DOI: 10.1055/s-0038-1647682
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alpha and Beta Receptor Stimulating and Blocking Agents on Experimental Disseminated Intravascular Coagulation

Abstract: SummaryIn this experimental study on rabbits, we compare the haemostatic and histological changes observed in animals with disseminated intravascular coagulation (DIC) induced by thrombin perfusion (100 u/kg/hr during 3 hours) with or without preventive administration of alpha and beta receptor stimulating or blocking agents.Both alpha and beta receptor stimulating agents enhance the disorders induced by thrombin alone, while alpha or beta blocking agents reduce them.This favourable action is still more pronou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The rise in the negative charge [5] and aggregation was reversed in vitro with -blocking agents, particularly with PRO, in a dose-dependent way (6,7). There were no species differences in the inhibition of platelet aggregation induced by -blockers in vitro.…”
Section: In Vitro Studies Bab Drugs and Platelet Aggregationmentioning
confidence: 82%
“…The rise in the negative charge [5] and aggregation was reversed in vitro with -blocking agents, particularly with PRO, in a dose-dependent way (6,7). There were no species differences in the inhibition of platelet aggregation induced by -blockers in vitro.…”
Section: In Vitro Studies Bab Drugs and Platelet Aggregationmentioning
confidence: 82%
“…More than the α-receptor sites may be involved, however. Moriau et al [158] observed an enhancement of artificial DIC (intra venous thrombin to rabbits) when either the alpha or the beta receptor sites were stimulated by metaraminol and isoproterenol, respectively, and more so still if both stimulators were used. Further, if the receptor sites were blocked-alpha by phentolamine and beta by practolol, singly or especially together-the DIC was minimized.…”
Section: Causes Of Icf Syndromesmentioning
confidence: 99%
“…In thromboembolic diseases accom panied by an elevated catecholamine level in blood, adrenaline-mediated platelet reactions may enhance the risk of thrombosis. As shown in animal experiments, catecholamines promote platelet aggregation in the microvasculature and increase experimental disseminated intra vascular coagulation (11,15,16,18,25). Therefore, tire pharmacological influence on adrenaline-induced changes in platelets pro vokes growing interest.…”
mentioning
confidence: 90%